A New Approach to the Derivation of Newton’s Law of Gravitation by Utilizing Kepler’s Laws - Amitabh Kumar (International Journal of Scientific Multidisciplinary Research, 2024)
This studies article explores a novel method to derive Newton’s Standard regulation of Gravitation by using utilising Kepler’s laws of planetary motion. Kepler's empirical laws provided the muse for information planetary orbits, but it become Newton’s formulation of the law of gravitation that unified those observations within a framework of classical mechanics. This observe revisits the connection between Kepler’s legal guidelines and Newton’s idea, presenting an alternative derivation primarily based on Keplerian standards. by way of reformulating key ideas in phrases of orbital dynamics and pressure interactions, this approach offers a clearer physical interpretation of ways Newton's inverse-rectangular law arises from Kepler's observations